Description of Self Awareness Diabetes Mellitus in Nursing Student of Faculty of Nursing Padjadjaran University - Mila Yudiana; Cecep Eli Kosasih; Hasniatisari Harun (University of Muhammadiyah Malang, 2019)
Diabetes mellitus was a disease that kept increased annually in the world. One of the factors that could prevent the occurrence of diabetes mellitus was self-awareness. The self-awareness for the students of nursing studies was very important to be developed, considering that nursing students were the prospective nurses which soon would become the role models in health and the nursing care givers. Thus, it was expected that the nursing students to have a high awareness. This research aimed to find out the description of self-awareness related to the risk factors of diabetes mellitus to the students of the Faculty of Nursing Universitas Padjadjaran. The method of the research was quantitative descriptive method that involved the population of the students of the Faculty of Nursing year 2014-2016 as much as 853 people, taken by simple random sampling method. The sample obtained was as much as 274 respondents. The data collection was by using self-awareness questionnaire, analyzed by frequency distribution method presented in the form of high, medium, and low self- awareness. The result of the research regarding the risk factors of diabetes mellitus were most of the respondents were included in the high category (55.20%), however, there were also respondents who were included in the medium category (47.44%). It can be concluded that there were respondents who have a medium self-awareness. Therefore, it is necessary to design the program to raise the self-awareness of nursing students related to diabetes mellitus risk factors.